The relationship between surgeon case load and revision rates in total hip arthroplasty: Evidence from the Swiss National Joint Registry - Andreas Ladurner; Karlmeinrad Giesinger; Bernhard Jost; Vilijam Zdravkovic (Swiss Medical Weekly)
STUDY AIMS: Higher surgeon volume has been correlated with improved therapy outcomes following total hip arthroplasty, and many countries have implemented minimum volume standards as a precondition for claiming reimbursement. However, there are large differences between healthcare systems worldwide and the applicability of international studies to a particular local healthcare environment may be limited. The aim of this study was to assess the relationship between surgeon case load (= number of procedures per year) and short-term revision rates (within two years of the index procedure) in patients undergoing primary total hip arthroplasty for hip osteoarthritis in a nationwide, registry-based study. In addition, the effects of increasing minimum volume standard thresholds on the potential reduction of the revision burden was simulated.